Increased Intra-Individual Variability as a Marker of Executive Dysfunction in Generalized Anxiety Disorder - Yu, Yongju; Xu, Haiyan; Xu, Yuanyuan; Lu, Fang; Li, Min (Frontiers in Psychiatry, 2022)
Recent studies have suggested that individual difference in intra-individual variability (IIV) of reaction times is an important indicator of attentional executive control. However, there are few existing studies on the executive control of high trait-anxious individuals assessed by using reaction time variability. This study assessed whether executive functions are impaired among clinical and nonclinical trait-anxious individuals indicated by IIV. The cross-reliability and discriminative power of three IIV parameters (raw intraindividual standard deviation, SD; reaction time coefficient of variation, RTCV; and mean absolute deviation, MAD) were compared. Twenty-five nonclinical individuals with low trait anxiety (LTA), 31 nonclinical individuals with high trait anxiety (HTA), and 19 clinical patients diagnosed with generalized anxiety disorder (GAD) finished self-reported measures, emotional spatial-cuing task, and nonemotional arrow flanker task. In the emotional task, GAD patients had significantly slower response speed, lower accuracy, and greater IIV parameters than the LTA and HTA groups. In the nonemotional task, the GAD group exhibited poorer processing efficiency, greater SD and RTCV, but intact performance effectiveness. RTCV was suggested to be a better marker of executive dysfunction than SD and MAD, due to its good discriminative power and reliability, as well as less affected by reaction times.